2022
DOI: 10.3390/s23010339
|View full text |Cite
|
Sign up to set email alerts
|

A Rapid Self-Alignment Strategy for a Launch Vehicle on an Offshore Launching Platform

Abstract: To reduce the impact of offshore launching platform motion and swaying on the self-alignment accuracy of a launch vehicle, a rapid self-alignment strategy, which involves an optimal combination of anti-swaying coarse alignment (ASCA), backtracking navigation, and reverse Kalman filtering is proposed. During the entire alignment process, the data provided by the strapdown inertial navigation system (SINS) are stored and then applied to forward and backtrack self-alignment. This work elaborates the basic princip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…The study indicated that during the launch of a sea-based launch vehicle, the transportation vessel's cooling can be achieved through the pumping and spraying of seawater, with the rate of water spray being optimally adjusted based on the launch vehicle's takeoff altitude to ensure maximum cooling efficiency. Mu et al [24] proposes a high-precision initial alignment method suitable for maritime launches, based on the optimal combination of anti-sway coarse alignment, retrograde navigation, and reverse Kalman filtering tailored to the characteristics of the marine environment. Xu et al [25] analyzed the motion performance of satellite launching platform with four different shapes of pontoons.…”
Section: Introductionmentioning
confidence: 99%
“…The study indicated that during the launch of a sea-based launch vehicle, the transportation vessel's cooling can be achieved through the pumping and spraying of seawater, with the rate of water spray being optimally adjusted based on the launch vehicle's takeoff altitude to ensure maximum cooling efficiency. Mu et al [24] proposes a high-precision initial alignment method suitable for maritime launches, based on the optimal combination of anti-sway coarse alignment, retrograde navigation, and reverse Kalman filtering tailored to the characteristics of the marine environment. Xu et al [25] analyzed the motion performance of satellite launching platform with four different shapes of pontoons.…”
Section: Introductionmentioning
confidence: 99%